The Relationship Between Acupressure Technique And The Reduction Of Nausea And Vomiting In Early Pregnancy - Faizal Akbar Farid Musliem (The International Journal of Medical Science and Health Research, 2026)
Introduction: Nausea and vomiting in early pregnancy (NVP), commonly known as morning sickness, is a prevalent condition affecting a majority of pregnant women, significantly impacting their quality of life. While often managed with dietary adjustments or pharmacological interventions, there is a growing interest in safe, non-invasive, and non-pharmacological alternatives. Acupressure, a traditional Chinese medicine technique applying pressure to specific acupoints, has emerged as a potential intervention, with the P6 (Neiguan) point being the most commonly targeted. This systematic review synthesizes the current evidence on the effectiveness of acupressure techniques for reducing NVP. Methods: A systematic review methodology was employed. Electronic databases were searched for studies published up to 2025. Studies were screened based on pre-defined criteria focusing on pregnant women in the first trimester experiencing NVP, interventions using pressure-based acupressure techniques, and designs including randomized controlled trials (RCTs), quasi-experimental studies, and systematic reviews. Data were extracted on study design, population characteristics, intervention protocols (points, method, duration), outcome measures, and results. The findings from 71 included sources were synthesized narratively and quantitatively where appropriate. Results: The synthesis of evidence from 71 studies, including RCTs, quasi-experimental designs, and meta-analyses, indicates that acupressure is an effective intervention for reducing NVP. The P6 point was the most frequently studied and demonstrated significant efficacy. Meta-analyses reported strong pooled evidence; for instance, one found acupressure reduced nausea (RR=0.47) and vomiting (RR=0.59) significantly (R. Helmreich et al., 2006). Quasi-experimental studies showed substantial pre-post symptom reductions (e.g., B. Devi, 2020). Acupressure was found effective for mild to moderate NVP, with emerging evidence supporting its use even in hyperemesis gravidarum (HG), particularly as an adjunct (Nor Azila Mohd Nafiah et al., 2022; H. Shin & Young A Song, 2005). Combination therapies with ginger or aromatherapy often yielded enhanced effects (Nikmah Jalilah Ritonga et al., 2020; Risa Ayu Faturanti et al., 2025). The safety profile was consistently favorable with minimal adverse effects. Discussion: The evidence supports acupressure as a viable, safe, and effective non-pharmacological option for managing NVP. Effectiveness appears influenced by symptom severity, methodological rigor, intervention protocol (e.g., continuous vs. intermittent application), and comparator type. While placebo effects may contribute, especially in unblinded studies, the consistent positive findings across diverse study designs strengthen the case for its clinical utility. Acupressure offers a practical, self-administerable option that aligns with patient preferences for minimal intervention during pregnancy. Conclusion: Acupressure, particularly at the P6 point, is recommended as an effective first-line or adjunctive intervention for reducing nausea and vomiting in early pregnancy, especially for women with mild to moderate symptoms. It presents a favorable safety profile. Future research should focus on standardized protocols, long-term effects, and cost-effectiveness to facilitate integration into routine prenatal care.